Nitrogen source and growth stage of Candida albicans influence expression level of vacuolar aspartic protease Apr1p and carboxypeptidase Cpy1p - Bauerová, Václava; Pichová, Iva; Hrušková-Heidingsfeldová, Olga (Canadian journal of microbiology, 2012)
Vacuoles play an important role in the physiology of pathogenic Candida spp. However, information on Candida albicans vacuolar enzymes, their properties, and regulation is scarce. Expression of the genes APR1 and CPY1 encoding vacuolar aspartic protease and serine carboxypeptidase, respectively, was analyzed using a clinical isolate of C. albicans. The transcription of both APR1 and CPY1 was upregulated in midexponential phase, together with increasing size of the vacuoles, when C. albicans was cultivated in yeast extract-peptone-dextrose agar at 30 °C. However, simultaneous upregulation of protein synthesis occurred only for Cpy1p. Analysis of APR1 and CPY1 expression under nitrogen-limited conditions revealed that the genes were regulated on both the transcriptional and translational levels and detectable amounts of Apr1p were synthesized only when C. albicans was grown in nitrogen-limited media.
Keywords: vakuoly; Aspartic Acid Proteases; Candida albicans; dusík; Culture Media; regulace genové exprese u hub; Nitrogen; Up-Regulation; Gene Expression Regulation, Fungal; Vacuoles; aspartátové proteasy; upregulace; karboxypeptidasy; Carboxypeptidases; kultivační média